COMPARISON OF THE EFFECTS OF PRE-EMPTIF ANALGESIA PREGABALINE 75 WITH 150 MG ON THE GRADE OF PAIN AND CAESARIAN SECTION SEDATION SCORE WITH SUBARAKHNOID BLOCK - Siradjuddin, Ardiansyah; Achmad, Muhammad Ramli; Gaus, Syafruddin (Jurnal Kesehatan, 2022)
In recent years, many studies have been carried out on the pre-emptive analgesia of pregabalin for various types of surgery with varying results. Preemptive analgesia in caesarean section (SC) usually uses pregabalin at a dose of 150 mg, and there have been no studies using low doses (75 mg) Objective This study aimed to determine the effects of pregabalin 75 mg vs 150 mg doses for controlled pain, their sedation score in patients after C-section under spinal anesthesia. Methods This study was a double-blind randomized trial study examining 20 samples of patients who underwent elective C-sections under spinal anesthesia and divided into 2 equal groups, P75 (who received oral pregabalin 75 mg) and P150 (who received pregabalin 150 mg). The Results There were no significant differences in NRS between the 75 vs 150 mg group (p>0.05), and there were significant differences in Ramsay sedation score between the 75 vs 150 mg group on 2 and 6 hours after surgery(p<0.05) and there were no significant differences about the need for fentanyl rescue between 75 vs 150 mg group (p>0.05). Pregabalin has an opioid-sparing effect and larger doses of pregabalin may increase its efficacy. The sedative effect that arises is due to the mechanism of action of pregabalin which binds potently to the 2δ subunit calcium channel and modulates calcium influx at nerve endings, thereby reducing the release of several excitatory neurotransmitters (glutamate), such as the mechanism of action of various intravenous and inhaled anesthetic agents. Preemptive administration of pregabalin 75 mg is recommended for C-section surgery because it might reduce NRS and the need for fentanyl rescue with minimal sedation side effects.